The Challenges in Village Fund Management in Enhancing Infrastructure Development and Community Empowerment in Nagari Muara Inderapura, Pesisir Selatan Regency - Wulandari, Sari Zaman; Malau , Hasbullah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to identify and analyze the challenges in optimizing village fund management in Nagari Muara Inderapura, Pesisir Selatan Regency. Village fund management plays a crucial role in supporting infrastructure development and community empowerment at the nagari level. However, its implementation still faces various challenges that hinder effective and targeted fund management. This research employs a descriptive qualitative method with a field study approach through interviews, observation, and documentation. The findings reveal several key challenges, including the lack of human resource skills, changes in village fund regulations, limited annual budget allocations, and insufficient workforce at the nagari level. On the other hand, infrastructure development has shown positive impacts on the community. These findings highlight the need to improve the capacity of nagari officials, ensure policy flexibility in fund allocation, and strengthen community participation in planning and implementation processes. The implications of this study emphasize that achieving optimal village fund management requires synergy between the nagari government, local communities, and higher-level authorities to ensure effective and sustainable village development.